Construção de uma revista de divulgação científica para o ensino fundamental ii como estratégia de sensibilização ambiental para a conservação de anfíbios - Oliveira, Raissa Marin de (Universidade Federal de São Carlos, 2022)
The Amphibia class is represented by the orders Gymnophiona, Caudata and Anura. In 2021, in Brazil, 1,188 species of amphibians were recognized. The group is quite diverse and presents several morphological and ecological contrasts. However, they represent the most endangered class among vertebrate animals, mainly due to human activities. The dissemination of popular beliefs and some tales and songs that promote the stigmatization of amphibians, generates damage to their conservation, as society does not realize the relevance of these animals to the environment. This work focuses on the process of creating a science magazine for elementary school students II, as well as the production of a board game for environmental awareness. The goalspecific of these materials is to present scientific information about general aspects of amphibians, ecological importance and the factors that are causing the decline of the class. The reading of science communication texts provides access to scientific knowledge in a simple way, the perception of science in everyday life and scientific literacy, as well as stimulates curiosity. Games, being a playful activity, are closely related to awareness processes, as they can also collaborate in the construction of knowledge. Through games, students develop different skills, such as: imagination, quick thinking, respect for rules and socialization. Thus, when associated with education, games help in social, affective, moral and cognitive development, generating several gains in the teaching and learning process.
Construction of a magazine of scientific dissemination for elementary education ii as a strategy for environmental awareness for amphibian conservation
Keywords: Educação Ambiental; Jogo de Tabuleiro; Anfíbio; Environmental Education; Board Game; Amphibian; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO